Naming the light : a week of years / Rosemary Deen. - Deen, Rosemary (Creative nonfiction (Urbana, Ill.), 1997)
Naming the Light is about places and people, books and music and travel, gardening and astronomy. Some essays examine Rosemary Deen's experience of finding herself well placed, at home in an old house with rambling gardens in New York's Catskill region. Others travel out to remote worlds, then bring them next door through the author's power of imagination. Deen sees human experience as part of a system alive with continuity between nature and culture - its worms and its cathedrals, its weather and its cantatas - all one, like a giant plant or a richly woven tapestry.